Synergetic effect as the basic factor of innovative development of domestic enterprises - Veremeenko, Alex (Management and Entrepreneurship: Trends of Development, 2017)
Purpose. The purpose is to study the interaction of key players in the innovation development of domestic industrial enterprises.Design/methodology/approach. The basic principles of the research are historical, systematic and comparative methods, institutional and structural-functional approaches have been used.Findings. The subject of the study are theoretical, methodological aspects and practical applications of the formation and implementation of innovative development of industrial enterprises. The paper deals with such tasks: the dynamics of the main indicators of the Ukrainian economy is analyzed, the features of the development of innovative activity of domestic enterprises are considered, the state and prospects for the development of state support for innovation activity are determined, the issue of financing innovative activity in Ukraine is noted.The article confirms that the introduction of innovations is an important and necessary condition for the effective economic development of business entities, taking into account their cumulative effectResearch limitations/implications. The paper diagnoses the problems of determining the cumulative effect from the introduction of innovative transformations.Originality/value. The scientific value and originality of the paper lies in the examination of the process of innovation activity of enterprises taking into account the interaction characteristics of its main participants. As a conclusion, the necessity to activate the innovative development of domestic industrial enterprises with the determination of the positive effect from their interaction and creation synergy is affirmed. In practice, this will help to increase the competitiveness of the Ukrainian economy and accelerate the process of integrating the country into the international environment